THE EXISTENCE OF NOTARY HONOR ASSEMBLIES IN THE CRIMINAL JUSTICE PROCESS - Erliyani, Rahmida; Ratomi, Achmad (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2018)
The aim of this study is to know and analyze the basic idea of the necessity for the approval of the Notary Honor Assemblies to the Notary examination in the criminal justice process and on the approval of the Notary Honor Assemblies to the Notary examination in the criminal justice process in relation to the principle fast, simple and low cost trial. This research uses doctrinal law research done or aimed at a concept that will be studied which is the concept or principle of fast, simple and low cost trial in relation with the authority of Honorary Notary Assembly to the checking of Notary in criminal justice process. The basic rationale of the existence of this NHA is the effort to enforce the obligation to deny or deny notary rights (the obligation to conceal the contents of the deed). Thus, the NHA’s approval as a opening “key” to the obligation of Notaries public when facing the complicated legal process. Legal protection of notary as regulated in Article 66 paragraph (1) law of the Repulic of Indonesia concerning Position of Notary (LPN) is a legal protection to notary public as a public official who is performing its task and obligation in carrying out government authority to keep the state documents in the form of authentic deed. The request for approval from NHA is not only done by the investigator at the stage of investigation, but will also be requested again by the prosecutor for the prosecution and by the judge for the court hearing not in accordance with one of the principles in the criminal justice process that is fast, simple and low cost court principle. For the seizure of the copy of the minuta deed and the summon to the Notaries must first the investigator, the prosecutor and the judge send the application for approval to NHA. It is said not to be in accordance with the simple justice principle because according to Article 66 Law of Position of Notary (LPN), the request for the approval of NHA is done at every stage of criminal justice process.